Post-traumatic arthritis of the sacroiliac joints mimicking inflammatory sacroiliitis: analysis of consecutive computed tomography examinations. Issue 6 (June 2020) - Rotem, G.; Herman, A.; Lidar, M.; Eshed, I.
Abstract : Aim: To assess the presence, prevalence and characteristics of post-traumatic, inflammatory-like changes of the sacroiliac joint (SIJ) on pelvic computed tomography (CT). Materials and methods: Sequential CT examinations from the acute (index) and follow-up post-traumatic periods of 24 patients that underwent pelvic trauma with SIJ involvement were evaluated and compared to 32 control patients with pelvic fractures that did not involve the SIJs. Index CT was evaluated for the presence of fracture, intra-articular step, and diastasis, whereas follow-up CT was scored for periarticular sclerosis, erosions, ankylosis, and backfill. Clinical follow-up was performed by pain provocation SIJ tests and a questionnaire (study representative subgroup, n =11, 46%) and from clinical files (control group, n =26, 31%). Pearson correlation coefficient was assessed between the index and follow-up CT variables. Linear regression was used to predict the influence of trauma variables on the development of inflammatory-like structural changes. Results: Total "structural, arthritis-like lesions' score from the follow-up CT examination was significantly higher in the study compared to the control group (3.25 versus 0.05 respectively, p <0.001). The presence of intra-articular diastasis and fracture were significant risk factors for the development of structural inflammatory-like lesions in the SIJ (1.19 and 2.1 respectively, p <0.001). Painful SIJs by physical examination were found in 50% of the clinically evaluated subgroup which was mechanical by nature in 81.8%. Conclusion: Traumatic SIJ fracture or diastasis is associated with the development of post-traumatic SIJ structural inflammatory-like lesions on pelvic CT, mimicking sacroiliitis. These findings may be the result of focal, post-traumatic joint inflammation, which leads to mechanical rather than inflammatory symptoms. Highlights: Structural inflammatory-like lesions may develop after sacro iliac joint trauma. Post traumatic structural inflammatory-like SIJ lesions may mimic sacroiliitis. SIJ post-traumatic lesions are not associated with inflammatory back pain.